2014
DOI: 10.1055/s-0034-1384851
|View full text |Cite
|
Sign up to set email alerts
|

Tanzsport: Verletzungsmuster im Lateinamerikanischen Formationstanz

Abstract: The injury profiles/patterns in Latin American formation dancing show on the one hand parallels to the individual partner dances. On the other hand, typical and gender-specific movement elements seem to reflect in the injuries and chronic damages/diseases of formation dancers. This is to be taken into account when injury prevention measures are considered. There is also a need for further studies to allow a more differentiated analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 5 publications
1
14
1
Order By: Relevance
“…This development seems to be necessary in order to remain competitive both on nationally and internationally. In addition to the high, often one-sided, loads, this results in a training time of up to 15 h weekly combined with only occasional professionalism and a not to be underestimated subordination of individual physical prerequisites to the benefit of group performance [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This development seems to be necessary in order to remain competitive both on nationally and internationally. In addition to the high, often one-sided, loads, this results in a training time of up to 15 h weekly combined with only occasional professionalism and a not to be underestimated subordination of individual physical prerequisites to the benefit of group performance [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mergenthaler [ 15 ] and Strauss [ 16 , 17 ] have already ranked formation dancing as the discipline with the highest injury risk within the various dance sports disciplines. Wanke et al [ 9 ] observed a possible correlation between gender-specific movement elements and injuries or chronic sports injuries in formation dance and pointed to a further need for research in this discipline.…”
Section: Introductionmentioning
confidence: 99%
“…The most common of which among dancers include “trying to ignore pain” and “continuing to dance”, irrespective of pain perception and even if pain is evaluated as “bad” . In case of complaints, self‐management is preferred to treatment by health professionals . As reasons for a lack of confidence in health experts, dancers expressed concerns that their existential and artistic needs are not understood or that they are not being adequately treated by health experts .…”
Section: Introductionmentioning
confidence: 99%
“…1,2,6,7,10,11 In case of complaints, self-management is preferred to treatment by health professionals. 1,8,10,12,13 As reasons for a lack of confidence in health experts, dancers expressed concerns that their existential and artistic needs are not understood or that they are not being adequately treated by health experts. 1,8,10,13 The described attitudes and behaviors concerning pain also seem to be present in non-professional dancers (Ds) and dance teachers (DTs) 8,[12][13][14] and can result in (further) injuries or a chronification of the symptoms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation